Boi-Bumbá de Parintins: heteronomia, competitividade e lazer na figuração de Caprichoso e Garantido - Joise Simas de Souza Maurício (2023)
The Parintins Folk Festival has been held since the 1960s in the city of Parintins-AM. Listed in 2018 by the National Historical and Artistic Heritage Institute (IPHAN) and has as its main element the Bois-Bumbás Caprichoso and Garantido that nourish a rivalry since its genesis, adapting and changing through the action of the civilizing process. From the physical clashes between the Bois in the streets to the symbolic, peaceful and admirable manifestation in the arena, we identify the relative autonomy of individuals in this process, however, heteronomous actions are also perceived, making figurations of peoplerules and also the state. The theoretical framework contemplates Norbert Elias with his procedural and figurational theory having as general objective to understand how the heteronomy was essential for the changes of the Boi-Bumbá who played in the terreiros until his protagonism that today stands out in the city of Parintins as Boi de arena. It is a research of qualitative approach, which had as method the Oral History with the accomplishment of 17 semi-structured interviews with residents of Parintins who participated or witnessed some event referring to the Boi-Bumbá since the first demonstrations in the city. The interviews were transcribed through the Transkriptor application, analyzed in the N-Vivo program and interpreted from the theoretical framework. In this way, we know the origin and duels between Bois-Bumbás Caprichoso and Garantido as a street folguedo, we record the memories of people about the process of insertion of Parintins Boi-Bumbá in a controlled space for disputes, evidenced how the control mechanisms present in the Boi de arena influenced the enjoyment of leisure and analyzed the changes in the Parintins Boi-Bumbá front of the demands of the State and society. We can then affirm the thesis that heteronomy permeates leisure activities, such as the Parintins Folk Festival, to meet the development of society where traditions undergo adjustments according to the requirements of the state and social relations to consolidate and remain alive in popular culture.